Clinical and epidemiological profile of patients hospitalized with tuberculosis at Hospital Regional João Penido in 2022 (Research, Society and Development, 2025)
Objective: To identify the clinical-epidemiological profile of patients hospitalized for tuberculosis at João Penido Regional Hospital during the year 2022. Material and Methods: This is an observational, cross-sectional study based on the retrospective collection of data from electronic medical records of patients hospitalized with tuber-culosis or diagnosed with tuberculosis during hospitalization in 2022. Results: Data from 86 medical records were collected, with the majority of patients being male (80.23%) and in the economically active age group. There was no significant variation in the ethnicities declared in the records, and most patients (88.37%) were from Juiz de Fora. Among the patients, 15 were institutionalized and 5 were homeless. The most common co-morbidity observed was systemic arterial hypertension (12.79%), while 18.60% of patients were HIV positive. The most prevalent clinical form of the disease was pulmonary tuberculosis (83.72%), and 81.40% of the cases were new diagnoses. The most common diagnostic method was sputum smear microscopy (AFB). Only 30 patients required oxygen therapy, and 22 patients needed intensive care. The most commonly used treatment regimen was the basic one (RIPE), and 73 patients were discharged with clinical improvement. Conclusion: Despite the various strategies implemented globally, nationally, and regionally for the prevention and control of tuberculosis, the results indicate that the region has not yet achieved the established goals. This highlights the need to intensify control actions and improve treatment adherence, with a focus on reducing the incidence rate and effectively eradicating the disease.